Report on Climate Bulletin Automation of the Ethiopian Meteorological Institute - Teshome, Asaminew; Mersha, Yonas; Demissie, Teferi Dejene (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The Ethiopian Meteorological Institute (EMI) is the only mandated institution by government proclamation that has the responsibility of providing raw, processed and analyzed meteorological data and interpreted weather and climate information in Ethiopia. The mission of EMI is to provide weather, climate and early warning services that contribute to socio-economic activities of the nation, and protect lives and property. In order to achive the afforemntioned mission, EMI is engaged in collecting, analyzing, forecasting and communicating meteorological and related information. The institute has three basic strategies; the first strategic is to ensure meteorological data coverage, quality and access across the country. Whereas, the second pillar is providing accurate and reliable meteorological forecast and early warning advisory service and the third focus is conducting Meteorological and related research activities to improve the forecasting and climate services in the country.